Health care USA : - Sultz, Harry A (Jones and bartlett, 1999)
New industry developments, health insurance changes, and major cost increases have significant implications for both providers and consumers. Changes in the Medicare program on which all other service charges are based, double digit premium increases by managed care companies, the growing number of uninsured, and a nation-wide movement among physicians to set up ambulatory diagnostic, surgical, and other treatment centers in competition with hospitals are changing the structure and operation of the U.S. health care system. The fifth edition of Health Care USA brings the reader up-to-date on these significant developments, as well as the technical, economic, political, and social forces responsible for these changes. Written from a public health or population perspective, new students of health administration will find this book exceptionally readable. Topics covered include: hospitals, ambulatory care, medical education, personnel, financing, managed care, long-term care, mental health services, research, the role of government, and much more.